Uses of dynamics of market price functions in products of Nepalese market - Sahani, Suresh Kumar; Sarswati Kumari Sah; Aafrin khatun; Kameshwar Sahani (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2025)
In this assignment, we addressed the usage of the dynamics of the market price function in 5 competitive products of the Nepalese market, which are handicrafts, tea and coffee, herbal products, honey, and agricultural products. The purpose of the study is to identify and analyze the market price dynamics of various products traded in the Nepalese market. This research method is entirely based on literature review. The following are the steps that will be taken: identification and search of literature, literature selection, literature analysis and synthesis, and conceptual framework. This article has applied differential equations to find the change in demand and supply due to price fluctuations. This research paper also demonstrates the speed at which the price adjusts towards its equilibrium value. The utilization of the market price dynamics function in the Nepalese market has a critical role. Market players, both producers, traders, and consumers, can use information about market price dynamics to make better decisions regarding production, trade, and consumption.